EFFECTS OF NEMATOPHAGOUS FUNGI ON VIABILITY OF EGGS AND JUVENILES OF MELOIDOGYNE INCOGNITA - M. Hussain; M. Zouhar; P. Ryšánek (Journal of Animal and Plant Sciences, 2017)
The present study was carried out to determine the efficacy of six fungal genera on the viability of eggs and second stage juveniles (J2) of Meloidogyne incognita. Cultures of all test fungi were prepared on potato dextrose agar (PDA). Lecanicilliummus carium was found to be highly effective in infecting eggs (79.6%), reducing egg hatching (6.9%), and causing the mortality of J2(78%), followed by L. psalliotae and Trichodermahamatum, compared to the controls. In contrast, Fusariumsolani demonstrated low infection of nematode eggs and J2. Aspergillus niger and A. nidulans did not show significant (P= 0.05) egg parasitism but these species were highly toxic againstJ2causing high mortality (50%).All the other fungal species showed moderate levels of infection of both eggs and J2. Our study demonstrated that L. Muscarium might be a potential biocontrol agent for the management of M. incognita, but further studies are needed to test its efficacy in the field.
Keywords: Parasitism; biocontrol agents; Lecanicilliummus carium; Fusariumsolani; Aspergillusniger